Phase shifting transformer to reduce power congestions and to redistribute power in interconnected systems - Ananda M. Halasiddappa; Malavalli R. Shivakumar (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The increased penetration of wind and solar power, as well as the liberalized electricity market, makes the power system network interconnected and complex. As the power demand is increasing daily, the complexity of operating large power systems is also increasing. Congestion in the transmission network may become more common than previously, making power flow management a problem that becomes increasingly important. Unexpected power flows (also known as loop flows) are becoming a bigger issue in today's linked power networks. These flows have a detrimental impact on the safe functioning of integrated power networks, which hinders their ability to conduct cross-border trade. Phase shifting transformers (PSTs) allow real power flow to be controlled by changing the phase shift across the device. This study deals with two interconnected parallel power system networks and the power flow controlled through a PST in between. The simulation results emphasize the importance of the PST in facilitating the transfer of energy throughout the regional transmission interconnection.